Application of Technological Innovations in Palm Sugar Processing in Gantarang Village, Sinjai Regency - Ichwan K, Muhammad; Bakri, Suardi; ., Herawaty; ., Syahidah; ., Makkarennu; Syahid, Muh. (Faculty of Engineering UNHAS, 2025)
This community service program was conducted in Gantarang Village, Sinjai Tengah District, Sinjai Regency—an area prone to landslides. The aim was to improve both the quality and quantity of palm sugar production through the adoption of modern and efficient processing technologies, ultimately enhancing community welfare. The program's partner was KTH Lestari, a local producer that previously relied on manual methods to make low-quality gula batok (molded palm sugar) with lengthy processing times. The initiative introduced product diversification in the form of gula semut (granulated palm sugar), supported by tools such as energy-efficient stoves, crystallization machines, and drying equipment, which accelerated the production process by up to 50%. Evaluation through pre- and post-tests revealed significant improvements: knowledge of gula semut rose from 36.4% to 100%, understanding of production equipment increased from 45.4% to 100%, and awareness of fermentation prevention techniques climbed from 18.1% to 72.7%. Daily production interest grew, and participants’ understanding of the economic potential of gula semut increased from 36.3% to 54.5%. The program also encouraged product innovation, including palm syrup and digital media utilization, with 54.5% of participants beginning to explore online marketing. Overall, the initiative strengthened the community’s technical skills and entrepreneurial capacity based on local commodities, supporting economic resilience in a disaster-prone area.